Application of IoT in Education (International Journal of Innovative Research in Computer Science & Technology, 2021)
Global communication among  individuals all over the globe has become a reality as the  global Internet has evolved through time. With the  growth of the Internet of Things, sentient, human-to machine, and device conversations have all been  transformed into interaction among everyone and  everything that is related to people, individual, and device  communications (IoT). As a result, the Internet of Things  has being enabled to capture all aspects of human life,  including safety and security, medical treatment, recycle,  ecological monitoring, and so on. This article discusses  the relevance of IoT technologies in the field of schooling  in terms of boosting the effectiveness of teaching and  learning. We look at it from several angles, such as  computer science training, medical, distance learning,  consumers environmental schooling, and so on. The  Internet of Things (IoT) in schooling has radically  changed educational institutions by allowing Web  connections amongst real things, sensors, and controllers.  By embedding detectors in products and merging cloud  computing, virtual reality, wearables, and big information  in this platform, many aspects of the learning atmosphere  may be observed and analyzed to provide relevant  information. It has also created a new link between  people and the environment in educational institutions.
Keywords: IoT; Smart Classroom; Internet; Connected devices; Education